Low Insulin-like growth factor I (IGF-I) level underlying recurrent infection in congenital cystic adenomatoid malformation (CCAM) and MyelodysplasticSyndrome with Chromosome 5q Deletion - U N Wijayanti (Medica Hospitalia : Journal of Clinical Medicine, 2015)
Background : Insulin-like growth factor I (IGF-I) is a polypeptide hormone produced mainly by the liver in response to the endocrine GH stimulus, but it is also secreted by multiple tissues for autocrine/paracrine purposes. IGF-I is partly responsible for systemic GH activities although it possesses a wide number of own properties (anabolic, antioxidant, anti-inflammatory and cytoprotective actions). IGF-I is a closely regulated hormone. Low IGF-1 level are observed in GH deficiency or GH resistence. If acquired in childhood, these condition result short stature. Currently the best characterized conditions of IGF-I deficiency are Laron Syndrome, in children; liver cirrhosis, in adults; aging including age-related-cardiovascular and neurological diseases; and more recently, intrauterine growth restriction. Most GH resistence in childhood is mild to moderate, with causes ranging from poor nutrition to severe systemic illness. The purpose of this case report is to summarize the decreasing list of roles of IGF-I underlying pathological desease. Case : The patients were hospitalized with short stature weight 18 kg, height 118 cm (under 3SD), The patient suffering chronic infection sience 2 years old with repeatly bronchiectasis infection. She has n't had menarche and episode Of hypoglycemia until nowand result examination Trigliseride : 95 mg/dl (normal : 30-150 ),Hemoglobin 8,1 g/dl, WBC 5,3 thousand/µl, Platelet 109 thousand/µl, Glucose 80 mg/dl, HDL: 21 mg/dl, LDL : 45 mg/dl, TSHs : 2,0 µIUmol/l, FT4: 12.16 ¾mol/l, Estradiol : < 11.80 pg/ml , FSH : 0.54 mlU/ml, LH : < 0.07 mlU/ml GH : 4.63 ng/ml, IGF-1 : < 25 ng/ml, Cranium scan no found tumor hypothalamic and pituitary, Bone marrow examination supports the diagnosis of MDS with multilineage dysplasia , MSCT of the thorax showed suspect cystic bronchiectasis, would be a Congenital Cystic AdenomatoidMalformation.and cytogenetic analized showed Chromosome number of single cell : 46, There were 20 cell been analized and 8 of cell were been counted Kariotipe : 46,XX,del 5q31. Conclusion : Low IGF-1 level in this patient due to severe systemic illness (recurrent infection of congenital cysticadenomatoid malformation (CCAM) and deletion 5qMyelodisplatia syndrome (MDS)and poor nutrition.